WHEN THIONAMIDES ARE CONTRAINDICATED: OUTCOME OF CHOLESTYRAMINE THERAPY IN HYPERTHYROID PATIENTS: A SINGLE TERTIARY CENTRE EXPERIENCE - Azman, Siti Sanaa Wan; Naidu, Thaalitha; Mokhtar, Muzhaffar bin; Ling, Tan Yee; Ali, Masliza Hanuni Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Cholestyramine, a bile acid sequestrant, binds to thyroid hormones in the intestine and enhances their clearance. Thionamides are the mainstay in the treatment of hyperthyroidism, however, this may not be an option in the presence of profound hepatitis and agranulocytosis. Here, we aim to assess the efficacy and tolerability of cholestyramine therapy in patients with hyperthyroidism where thionamides are contraindicated. METHODOLOGY A one-year retrospective review of patients with hyperthyroidism who were treated with cholestyramine was performed from April 2023 to April 2024. RESULT A total of 10 patient medical records (8 females and 2 males) were reviewed. The mean age was 51.7 years old and the median duration of hyperthyroidism was 7.5 years. Graves’ disease was the underlying aetiology in 7 cases, and the rest was a toxic multinodular goitre. Six of our patients already had atrial fibrillation, with four of them having cardiomyopathy. The reason for conversion from carbimazole to cholestyramine was transaminitis for one patient, and the remaining was due to neutropenia and thrombocytopenia. Seven patients (70%) received Lugol’s iodine for not more than 10 days, relying on its WolffChaikoff effect. One patient received prednisolone as an adjunct therapy for hyperthyroidism. The total daily dose of cholestyramine commenced was 12 g given in TDS dosing for a median duration of 1.4 months. Median FT4 level preand post-cholestyramine therapy were 50.2 pmol/L and 25.5 pmol/L respectively (NR 7.86-14.41), p = 0.028. The median TSH level was <0.005 m IU/L. We were able to rechallenge six patients (60%) with carbimazole as they showed an improvement in their laboratory parameters. Only two patients underwent subsequent definitive therapy with RAI and thyroidectomy. None of our patients developed any adverse side effects from cholestyramine. CONCLUSION Our experience demonstrated that in selected cases, cholestyramine may be used as an effective and welltolerated therapy when first-line options are contraindicated.